2022
DOI: 10.3390/su14031173
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships among Microelement Composition of Reindeer Meat (Rangifer tarandus) and Adaptation: A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis based on PRISMA statements aimed to summarise the data on the chemical composition of reindeer meat depending on the region of the Rangifer tarandus. We searched SCOPUS, PubMed, Embase, CrossRef, Medline, Cochrane library, eLibrary, and CyberLeninka. A total of 3310 records published between January 1980 and December 2021 were screened. We identified 34 relevant studies conducted in Russia, Norway, the USA, Canada, and Finland for the synthesis. Overall, the consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The shortage of Ca [119] and K [120][121][122] in the water also impacts the reduction of cardiovascular diseases. Consuming local fish and venison can compensate for the shortage of Ca, Mg, K, Cu, etc., [41,42], which is limited in the drinking water in the YNAO and contributes to decreasing health risks.…”
Section: Impacts Of Changing Water Quality On the Health And Wellbein...mentioning
confidence: 99%
See 1 more Smart Citation
“…The shortage of Ca [119] and K [120][121][122] in the water also impacts the reduction of cardiovascular diseases. Consuming local fish and venison can compensate for the shortage of Ca, Mg, K, Cu, etc., [41,42], which is limited in the drinking water in the YNAO and contributes to decreasing health risks.…”
Section: Impacts Of Changing Water Quality On the Health And Wellbein...mentioning
confidence: 99%
“…These micronutrients play a central role in the regulation of blood pressure [40]. Long-term intake of ultra-fresh water does not affect human health if a significant amount of local fish and venison is consumed [41], as this is beneficial due to containing sufficient amounts of the trace elements lacking in pure water [42].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the review papers included in this Special Issue, two investigations can be found that address the following themes: the evaluation of the relationship between negative affect and maladaptive eating behavior as a regulation strategy in normal-weight individuals [9] and a summary of the data on the chemical composition of reindeer meat depending on the region of the Rangifer tarandus-a systematic review and meta-analysis [10].…”
mentioning
confidence: 99%
“…, many experts mentioned the previous fruitful experience of the collaboration with researchers while participating in joint projects with the YNAO Arctic Scientific Research Centre, Association of Reindeer Herders in YNAO, Naryan-Mar Agriculture Research Station, N. Laverov Federal Center for Integrated Arctic Research of the Ural Branch of the Russian Academy of Sciences, Federal Research Centre "Kola Science Centre of the Russian Academy of Sciences", and Northern Arctic Federal University. For example, those that resulted in jointly developed strategies for the Lovozero district and Loparskaya, different districts of YNAO and NAO[98], such as recommendations for reindeer herders and producers of reindeer meat[99,100] and developed programmes on promoting healthcare facilities for the Indigenous communities[101], etc. It signifies scientific research has a role in "providing authorities with methodologies and data for quick response to changes in the living standards and life strategies of the Indigenous population"[102] (p. 2888).…”
mentioning
confidence: 99%